Assessing the influence of the coffee cup on the multisensory tasting experience - Spence, C; Carvalho, F (Elsevier, 2019)
This review summarizes the latest evidence concerning the impact of the colour, shape, texture, weight, and other material properties of the drinking receptacle on the perception of coffee. The colour of the cup, for instance, has been shown to prime notions of sweetness (e.g., pink cup) or acidity (e.g., yellow or green cup) that may carry over to influence the tasting experience. Meanwhile, the shape and surface feel of the drinking vessel have also been shown to exert a profound influence over the perceived aroma/taste of coffee. Given that the various sensory attributes of the drinking vessel can exert such a striking influence over the drinking experience, the challenge, moving forward, is to optimize the design of the receptacle in order to enhance the multisensory tasting experience for the consumer. Given that different styles/varieties of specialty coffee have different dominant/desirable qualities (e.g., acidity/sweetness), in the future, the design of coffee cups may need to be customized for different coffee drinking experiences (e.g., origin or roast), much as seen in the world of fine wine (with different glasses for different grape varieties).